The Human Nature Dialogue In the Poetry of Robert Frost: Major Themes: Exploring the relationship between man and nature in Robert Frost's poetry (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Although Robert Frost did not consider himself a "naturepoet,” did not like to be called one, and would point out the information thatall but a few of Ms poems have people in them, his feeling for nature wasobviously a very close one. Many critics of Robert F rost ' s poems, however,have not understood his position. In 1938,, Robert P. Trist r am Coffin statedthat Frost presents nature with people stuck into it where they belong and thathe treats of people in a state of only good nature, views which now seem f a rf r om accurate, as most critics agree. Robert J Langbaum remarked that Frostmakes man and nature interweave so that they seem identical, an opinion thatignores the individuality of Frost’s character.